Pemberdayaan Masyarakat Melalui Inovasi Produk Lokal Studi Kasus: Pengelolaan Buah Sawo Menjadi Bolu Kukus di Desa Kaligelang - Ismanto Ismanto; Muhammad Ilham Saputra; Nur Annisa Ariyanti; Jainul Jainul; Aisyah Muttawaroh; Aisyah Nurul Fadilah; Ahmad Silahuddin Al Ayubi; Desty Anni Safitri; Leni Tri Wibowo; Mili Satriska; Melani Arbayah; Reija Auladi Salsabil; Via Qotrunada Afifa (FKIP, Universitas Palangka Raya, 2024)
The sapodilla fruit, as a tropical fruit rich in nutrients, holds significant economic potential in Kaligelang Village, Pemalang Regency. Despite producing high-quality fruit, the utilization of sapodilla in this village is still limited to direct sales without further processing. This study aims to enhance the knowledge and skills of the members of the PKK (Family Welfare Program) in processing sapodilla into steamed cake (bolu kukus) as an innovative value-added product. A processing demonstration was conducted on September 20, 2024, with 32 participants involved. The research method utilized pre-test and post-test questionnaires, which were analyzed using N Gain Score to measure the effectiveness of the training. The results showed an average increase of 23.69 points in participants' knowledge scores, with an average N Gain Score of 0.43, categorized as moderate. The findings indicate that this program not only enhances participants' knowledge but also has the potential to strengthen the local economy through the development of sapodilla-based small and medium enterprises (UMKM).